Religion and politics in the Islamic world (Eurasian Journal of Religious Studies, 2017)
The main platform that unites the Islamic countries of the world on a religious basis is Islam. Often talk about the importance of Islamic values for the Muslim world, in order to cultivate the spiritual culture and socio-political life of Muslim countries. Secular and religiously oriented politicians, who revived the tradition of the early Islamic, showed that the only way for the Arab world is to follow the Muslim way of life. Among these concepts of Islamic sociology, the Islamic economy and the Islamic state, it is assumed that traditional Islamic values will correspond to the current state of the country and modernize the political and socio-economic situation. That is, this article is a systematic analysis taking into account the real situation when studying the relationship between religion and the state in the modern Islamic world.